Retrofit of hydrogen-powered helicopters: An optimal approach - Nesci, A.; Vicenzotti, G.; Brunetti, M.; Salucci, F. (My University, 2022)
In the framework of developing a climate-neutral aviation industry, hydrogen could play a critical role in the future. Given hydrogen’s high specific energy but fuel cells’ low specific power, this technology can be effectively used in conjunction with batteries, which have opposing characteristics. To that end, it is critical to develop design methodologies that allow for effective component integration and weight optimization. Therefore, this article introduces an original algorithm, HERACLES, which solves a constrained non linear optimization problem, aiming to find the lightest hydrogen-driven powertrain able to replace the conventional thermal engine-driven powertrain of a generic rotorcraft, preserving its given Maximum Take Off Weight (MTOW) and airframe. In order to demonstrate the effectiveness of the methodology, this is applied to a reference helicopter representative of the heavy category, MTOW of about 9 ton, considering a FC-based architecture. The optimal results are presented and then compared to a first sizing guess, showing the improvements on the payload obtainable with a better system integration. Finally, some sensitivity studies are carried out to picture the impact of the main technological key performance indexes on aircraft payload.